Charting a Course for the Future of Maine’s Fisheries: An Interview with Commissioner Robin Alden - Alden, Robin (Maine Policy Review, 1996)
In a January, 1996 interview, Commissioner of the Maine Department of Marine Resources, Robin Alden shared her concerns about the direction of federal fisheries management and her goals for building a more dynamic and self-managing system here in Maine. In particular, Alden described the recent legislation which creates zone councils and an apprenticeship system in Maine’s lobster fishery. Alden articulated a direction for Maine’s fisheries that challenges conventional fisheries management and as such, is being watched closely by fisheries managers in Maine as well as elsewhere in the U.S. and overseas.